Effect of Chromium on Glucose and Lipid Profiles in Patients with Type 2 Diabetes; A Meta-analysis Review of Randomized Trials - Mohammad Abdollahi; Amir Farshchi; Shekoufeh Nikfar; Meysam Seyedifar (Frontiers Media S.A., 2013)
Purpose. Chromium (Cr) as an essential trace element in metabolism of carbohydrate, lipid and protein is currently prescribed to control diabetes mellitus (DM). The objective of this meta-analysis was to compare the effect of Cr versus placebo (Pl) on glucose and lipid profiles in patients with type 2 DM. Methods. Literature searches in PubMed, Scopus, Scirus, Google Scholar and IranMedex was made by use of related terms during the period of 2000-2012. Eligible studies were randomized clinical trials (RCTs) with intake of Cr higher than 250 µg at least for three months in type 2 DM. Glycated hemoglobin (HbA1c), fasting blood sugar (FBS), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), very low-density lipoprotein cholesterol (VLDL-C), triglyceride (TG), and body mass index (BMI) were the main outcomes. Results. Seven out of 13 relevant studies met the criteria and were included in the meta-analysis. HbA1c change in diabetic patients in Cr supplement therapy comparing to Pl was -0.33 with 95%CI= -0.72 to 0.06 (P= 0.1). Change of FBG in Cr therapy vs. Pl was -0.95 with 95%CI= -1.42 to -0.49 (P< 0.0001). TC change in Cr therapy vs. Pl was 0.07 with 95%CI= -0.16 to 0.31 (P= 0.54). TG change in diabetic patients in Cr supplement therapy comparing to Pl was -0.15 with 95%CI= -0.36 to 0.07 (P= 0.18). Conclusions. Cr lowers FBS but does not affect HbA1c, lipids and BMI. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.